(х-12)(3-х)=0 -0,8(х-1.5)=6,4 /3 9\ l- х - - l (0,8+х)= \8 16/

kuklas228 kuklas228    1   18.05.2019 01:10    0

Ответы
mariagievich mariagievich  11.06.2020 06:04

x-3)(x+12)=0
x2(квадрат)+12x-3[-36=0
x2+9x-36=0
D=81+144
D=225
x=-b+-КореньD/2a
x(первое)=-9+15/2=3
x2=-9-15/2=-12

ответ: x1=3
x2=-12

ПОКАЗАТЬ ОТВЕТЫ
JollyWolf JollyWolf  11.06.2020 06:04

x-3)(x+12)=0 
x2(квадрат)+12x-3[-36=0 
x2+9x-36=0 
D=81+144 
D=225 
x=-b+-КореньD/2a 
x(первое)=-9+15/2=3 
x2=-9-15/2=-12 

ответ: x1=5
x2=-17

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика